Perancangan Furniture Kamar Hotel Berbahan Dasar Bonggol Jagung - hany alatas; Andry (Jurnal Desain Produk Nasional, 2023)
This research is the design of hotel room furniture products that use corn cobs as the main material. This research was conducted because furniture is an important part of a hotel room. Each hotel generally has a bed, bar table,dressing table, chair, and bedside table. In this study, the bedside table product was chosen because this product is often used in hotel rooms. In addition, corn cob material was chosen because it is usually only used as animal feed and has not been used as a basic material for hotel furniture. This material has a unique texture and pattern that gives it a different characteristic from hotels in general, which usually only use wood, bamboo, or rattan as the basic material for furniture. This research begins with determining the hotel where the research will be carried out. After several considerations, the Le Aman Bali Hotel was chosen. Hotel Le Aman Bali was chosen because the hotel is currently carrying out furniture replacement and it is hoped that this study can provide added value, uniqueness, and characteristics that will have a positive impact on the hotel. Then an in-depth study is carried out to better identify the hotel that will be carried out according to the theme and needs of the hotel. Then an alternative sketch was made, in which from several alternative sketches three designs were selected to enter the next stage, namely making a prototype. Prototype-making is done utilizing the lamination method. This method was chosen because it was adapted to the needs of the product, especially in making the table to be used. The novelty of this research is corncobs as the main material for making furniture at the Le Aman Bali Hotel.